Differential Biological and Adjuvant Activities of Cholera Toxin and Escherichia coli Heat-Labile Enterotoxin Hybrids - Bowman, Christal C. (American Society for Microbiology, 2001)
Two bacterial products that have been demonstrated to function as mucosal adjuvants are cholera toxin (CT), produced by various strains of Vibrio cholerae, and the heat-labile enterotoxin (LT) produced by some enterotoxigenic strains of Escherichia coli. Although LT and CT have many features in common, they are clearly distinct molecules with biochemical and immunologic differences which make them unique. The goal of this study was to determine the basis for these biological differences by constructing and characterizing chimeric CT-LT molecules. Toxin gene fragments were subcloned to create two constructs, each expressing the enzymatically active A subunit of one toxin and the receptor binding B subunit of the other toxin. These hybrid toxins were purified, and the composition and assembly of CT A subunit (CT-A)-LT B subunit (LT-B) and LT A subunit (LT-A)-CT B subunit (CT-B) were confirmed. Hybrids were evaluated for enzymatic activity, as measured by the accumulation of cyclic AMP in Caco-2 cells, and the enterotoxicity of each toxin was assessed in a patent-mouse assay. The results demonstrated that LT-A–CT-B induces the accumulation of lower levels of cyclic AMP and has less enterotoxicity than either wild-type toxin or the other hybrid. Nonetheless, this hybrid retains adjuvant activity equivalent to or greater than that of either wild-type toxin or the other hybrid when used in conjunction with tetanus toxoid for intranasal immunization of BALB/c mice. Importantly, the ability of LT to induce a type 1 cytokine response was found to be a function of LT-A. Specifically, LT-A–CT-B was able to augment the levels of antigen-specific gamma interferon (IFN-γ) and interleukin 5 to levels comparable to those achieved with native LT, while CT-A–LT-B and native CT both produced lower levels of antigen-specific IFN-γ. Thus, these toxin hybrids possess unique biological characteristics and provide information about the basis for differences in the biological activities observed for CT and LT.